HLA-Class II Artificial Antigen Presenting Cells in CD4+ T Cell-Based Immunotherapy - Couture, Alexandre; Garnier, Anthony; Docagne, Fabian; Boyer, Olivier; Vivien, Denis; Le-Mauff, Brigitte; Latouche, Jean-Baptiste; Toutirais, Olivier (Frontiers in Immunology, 2019)
CD4+ T cells differentiate into various T helper subsets characterized by distinct cytokine secreting profiles that confer them effector functions adapted to a variety of infectious or endogenous threats. Regulatory CD4+ T cells are another specialized subset that plays a fundamental role in the maintenance of immune tolerance to self-antigens. Manipulating effector or regulatory CD4+ T cells responses is a promising immunotherapy strategy for, respectively, chronical viral infections and cancer, or severe autoimmune diseases and transplantation. Adoptive cell therapy (ACT) is an emerging approach that necessitates defining robust and efficient methods for the in vitro expansion of antigen-specific T cells then infused into patients. To address this challenge, artificial antigen presenting cells (AAPCs) have been developed. They constitute a reliable and easily usable platform to stimulate and amplify antigen-specific CD4+ T cells. Here, we review the recent advances in understanding the functions of CD4+ T cells in immunity and in immune tolerance, and their use for ACT. We also describe the characteristics of different AAPC models and the way to improve their stimulating functions. Finally, we discuss the potential interest of these AAPCs, both as fundamental tools to decipher CD4+ T cell responses and as reagents to generate clinical grade antigen-specific CD4+ T cells for immunotherapy.